Ответ:
Объяснение:
1. а=-2, b=1
2*(-2)(-2-1)=-4*(-3)=12
2. a=0, b=3
2*0*(0-3)=0
3. a=3, b=0
2*3(3-0)=6*3=18
4. a=5, b=7
2*5*(5-7)=10*(-2)=-20
5. a=5, b=-2
2*5(5-(-2))=10*7=70
6. a=6,b=2
2*6*(6-2)=12*4=48
7. a=10, b=7
2*10*(10-7)=20*3=60
8. a=-10, b=-7
2*(-10)*(-10-(-7))=-20*(-10+7)=-20*(-3)=60
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
Объяснение:
1. а=-2, b=1
2*(-2)(-2-1)=-4*(-3)=12
2. a=0, b=3
2*0*(0-3)=0
3. a=3, b=0
2*3(3-0)=6*3=18
4. a=5, b=7
2*5*(5-7)=10*(-2)=-20
5. a=5, b=-2
2*5(5-(-2))=10*7=70
6. a=6,b=2
2*6*(6-2)=12*4=48
7. a=10, b=7
2*10*(10-7)=20*3=60
8. a=-10, b=-7
2*(-10)*(-10-(-7))=-20*(-10+7)=-20*(-3)=60